Leadership of the School Principle in Developing Teacher Professionality at SDIT Az-Zahra Sragen - Moh. Firman*; Andi Arif Rifa'i (Riwayat: Educational Journal of History and Humanities, 2023)
This study aims to describe: 1) Principal leadership in developing teacher professionalism at SDIT Az-Zahra Sragen. 2) Obstacles and suggestion in developing teacher professionalism. This study used a qualitative descriptive approach which was carried out at SDIT Az-Zahra Sragen from January to June 2022. The subjects of this study were the Head of SDIT Az-Zahra Sragen, the informants were vice principal teachers and Al-Falah Foundation Sragen in the field of education. Data collection techniques with the method of observation, interviews and documentation. Data analysis using data collection methods, data reduction, data presentation and drawing conclusions. The results of the study show that: First, the principal of SDIT Az-Zahra Sragen has carried out teacher professionalism well, as evidenced by careful planning, structured management, quality human resource development, and tight control. Second, the obstacles encountered are: lack of motivation, especially teachers who are over 35 years of age to develop their professional competence, teachers do not understand good communication techniques, teachers on leaveand many teacher activities outside of school so they take leave. Third, the solution to dealing with obstacles is by holding workshops and training, holding activities to increase social and communication skills, recruiting temporary teachers whose job is to replace teachers who is on leave.